ҚАСЫМ ӘЎЕЗОВ – МӘМЛЕКЕТЛИК ҒАЙРАТКЕР (1930-1936-ЖЫЛЛАР) - Матсалаева, Г. (FAN va JAMIYAT, 2022)
In our article defiues the work done in 1930-1936 during the life of a major statesman of Karakalpakstan, Kasym Avezov. Written sources are also analyzed related to this period.